2015
DOI: 10.4137/bci.s31353
|View full text |Cite
|
Sign up to set email alerts
|

Arabinosylation Plays a Crucial Role in Extensin Cross-linking In Vitro

Abstract: Extensins (EXTs) are hydroxyproline-rich glycoproteins (HRGPs) that are structural components of the plant primary cell wall. They are basic proteins and are highly glycosylated with carbohydrate accounting for >50% of their dry weight. Carbohydrate occurs as monogalactosyl serine and arabinosyl hydroxyproline, with arabinosides ranging in size from ~1 to 4 or 5 residues. Proposed functions of EXT arabinosylation include stabilizing the polyproline II helix structure and facilitating EXT cross-linking. Here, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 68 publications
2
23
0
Order By: Relevance
“…As shown in Figure 5, the latter two families were found mainly in the trans-Golgi whereas GAUTs were in the cis/medial-Golgi. Several of the cis-Golgi-localized ( Figure 5) P4H enzymes catalyze the first step in O-linked glycosylation and shuttle between the ER and the cis-Golgi (Yuasa et al, 2005;Velasquez et al, 2011), while the medial RRA3 (M4 in Figure 5A) catalyzes the subsequent arabinosylation of Hyp (Chen et al, 2015). Some S-adenosyl-methionine (SAM)-dependent methyltransferases have been associated with methyl esterification of substrates synthesized by GAUT1 and GAUT7 (Krupková et al, 2007;Miao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 5, the latter two families were found mainly in the trans-Golgi whereas GAUTs were in the cis/medial-Golgi. Several of the cis-Golgi-localized ( Figure 5) P4H enzymes catalyze the first step in O-linked glycosylation and shuttle between the ER and the cis-Golgi (Yuasa et al, 2005;Velasquez et al, 2011), while the medial RRA3 (M4 in Figure 5A) catalyzes the subsequent arabinosylation of Hyp (Chen et al, 2015). Some S-adenosyl-methionine (SAM)-dependent methyltransferases have been associated with methyl esterification of substrates synthesized by GAUT1 and GAUT7 (Krupková et al, 2007;Miao et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was found that intra-and inter-molecular cross-linking took place in glycosylated HRGPs under the catalysis of the peroxidase. However, the deglycosylated HRGPs could not be cross-linked [18], suggesting that glycosylation contributes to the HRGPs network formation.…”
Section: Physical Barriermentioning
confidence: 96%
“…In plants, hydroxyproline-rich glycoproteins (HRGPs) which are characterized by a rigid polyproline type II (PPII) conformation and extensive O-glycosylation of 4 (R)-hydroxy-l-proline residues [87], can physically inhibit pathogen penetration [88]. HRGPs play a leading role in plant defense, e.g., HRGPs were induced in incompatible plant-pathogen interactions [18,89] and rapidly deposited in the cell wall after pathogen infection [90,91]. Such a defense ability is a result of the intra-and inter-molecular cross-linking in plant cell walls after HRGPs become insolubilized [88,92].…”
Section: Physical Barriermentioning
confidence: 99%
“…For example, UDP-Xyl is essential for the xylosylation of Notch signaling receptors (Lee et al, 2013 ), and initiates the core protein linkage in the proteoglycans heparin, chondroitin and dermatan sulfate (Esko et al, 2009 ; Beahm et al, 2014 ). UDP-Ara is a donor molecule for structural extensin glycoproteins in plant cell walls (Chen et al, 2015 ), and arabinose chains on therapeutic antibodies expressed in plant-based systems (Dicker et al, 2016 ). Despite their role in diverse and health-related processes, convenient preparations of UDP-Xyl and UDP-Ara are still not generally well-established and ready to meet the needs of a growing glycoscience community (Pauly et al, 2000 ; Kotake et al, 2009 ; Damerow et al, 2010 ; Yang and Bar-Peled, 2010 ; Gu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%